Forging economic resilience in the People Republic of China through value chain upgrading and economic rebalancing. - Mariasingham, Mahinthan J.; Alvarez, Julian Thomas B.; Antonio, Gienneen G.; Consing, Rafael Martin M. III (Metro Manila, Philippines Asian Development Bank, 2021)
The brief examines how the PRC has upgraded its role in global value chains and transitioned toward more localized production networks with the support of its massive and rapidly growing domestic consumption base. It also discusses how the coronavirus disease (COVID-19) crisis has sped up two of the most significant trends that have reshaped global value chains in recent years: the digitalization of trade and the reconfiguration of production networks closer to consumer markets.
Keywords: Financial institution; Finance; Electronic books